2002
DOI: 10.1038/sj.onc.1206030
|View full text |Cite
|
Sign up to set email alerts
|

The Sp1 transcription factor contributes to the tumor necrosis factor-induced expression of the angiogenic factor thymidine phosphorylase in human colon carcinoma cells

Abstract: Thymidine phosphorylase (TP; also known as plateletderived endothelial cell growth factor, PD-ECGF) is an angiogenic factor that is chemotactic for endothelial cells and has been found to induce neovascularization in vivo. TP is frequently overexpressed in human solid tumors, where its expression has been correlated with increased tumor microvessel density, invasion, and metastasis, and shorter patient survival. In this report, TP activity in the WiDr colon carcinoma cell line was found to be induced 100-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 51 publications
5
39
0
Order By: Relevance
“…In the tumor microenvironment, TNFa mediates cancer-related inflammation, and may promote tumor progression by increasing angiogenesis and metastasis. [1][2][3]25 The levels of TNFa [6][7] and its downstream genes c-FLIP 18,29 and thymidine phosphorylase [19][20][21][22] are known to be elevated in nasopharyngeal carcinoma tumor tissues. Here, we used Affymetrix chips to identify the 10 TNFa-inducible genes showing the highest upregulation in nasopharyngeal carcinoma tissues vs normal adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the tumor microenvironment, TNFa mediates cancer-related inflammation, and may promote tumor progression by increasing angiogenesis and metastasis. [1][2][3]25 The levels of TNFa [6][7] and its downstream genes c-FLIP 18,29 and thymidine phosphorylase [19][20][21][22] are known to be elevated in nasopharyngeal carcinoma tumor tissues. Here, we used Affymetrix chips to identify the 10 TNFa-inducible genes showing the highest upregulation in nasopharyngeal carcinoma tissues vs normal adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the various TNFa-regulated genes that appeared to be upregulated in nasopharyngeal carcinoma tumor cells vs adjacent normal tissues, and found differential expression of various TNFa target genes MMP9, 12 MMP12, 13 MMP14, 14 BIRC5, 15 CXCL13, 16 IL12B, 17 c-FLIP, 18 and thymidine phosphorylase. [19][20][21] We further showed that the upregulation of thymidine phosphorylase in nasopharyngeal carcinoma tumor cells resulted at least in part from cytoplasmic heterogeneous nuclear ribonucleoprotein K (hnRNP K)-mediated stabilization of the thymidine phosphorylase mRNA. 22 High levels of thymidine phosphorylase and cytoplasmic hnRNP K were significantly correlated with overall survival and distant metastasis.…”
mentioning
confidence: 98%
“…Thus, our results strongly support a novel function of cytoplasmic hnRNP K in the stabilization of TP mRNA through the binding of hnRNP K to the CURE element at the 3 0 end of the TP mRNA. Although TP gene expression has been shown to be regulated by the Sp1 and STAT transcription factors (Zhu et al, 2002;Yao et al, 2005), the mechanisms of TP mRNA stabilization induced by interferon-a, -b and -g have yet not been fully elucidated (Schwartz et al, 1998;Yao et al, 2005). We herein show that TP is a new target for cytoplasmic hnRNP K, providing insight into the mystery of TP mRNA stabilization and perhaps explaining the regulation of TP mRNA stability in response to interferon-a, -b and -g.…”
Section: Discussionmentioning
confidence: 99%
“…TP expression is transcriptionally controlled by the transcription factors, Sp1 and STAT (Goto et al, 2001;Zhu et al, 2002;Yao et al, 2005), and posttranscriptional regulation of TP mRNA stability has been proposed in response to interferons (Schwartz et al, 1998;Yao et al, 2005). However the molecular mechanisms underlying the posttranscriptional regulation have not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a number of genes that can mediate angiogenesis have been shown to be modulated by Sp1, including VEGF (34), thymidine phosphorylase (48), and metalloprotease 2 (49).…”
Section: Bcl-2 In Upar Expression and Sp1 Transcriptional Activitymentioning
confidence: 99%